Village Bankers : The Experience of Fandene (Senegal) - Easton, Peter (World Bank, Washington, DC, 2012)
The experience of the locally-created credit, and savings institution in Fandene, Senegal, is shared in this note. Its structure grew essentially out of local responses to the problems of drought, and diminished farm fertility throughout central Senegal, and, it is the product of historical interactions: the largely Christian community shares resources with the neighboring valley, and river beds of Islamic communities of different ethnic groups. The "Association des Jeunes de Fandene" (AJF), or the Fandene Young People's Association, was created in 1972, concentrating initially in sponsoring cultural events, which lead to educated young people to constitute a group of "modern" peasantry. This effort later evolved into initiatives to diversify the local economy, and improve the natural resource base. But these efforts were hampered by inadequate access to credit, and resources to implement development. The AJF looked at resolving the bottleneck of credit, and eventually created local savings and loan committees, to support economic innovations. Most impressive were the institution-building results, sharing governance of their activities, and resources, where both women, and men's branches exercise equal weight. Moreover, marketing arrangements have been developed with other peasant federations, and, technical teams created, to support emerging needs in nearby poor neighborhoods.